From Sensors to Safety: IoT-Enabled Smart Helmets as a Game-Changer for Worker Protection in High-Risk Industries - Budiono, Christiano Evan; Nul Arif, Hendri Lukman; Kencana Efendi, Sekar Galih; Ramadani, Nadia Ayu; Hendrawan, Nailyaa Faza; Mirachel Prakusya, Nabila Levi; Zannah, Qoridhatul; En Nabhan, M. Zuhair; Dwianti , Aigies Siska (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2025)
The integration of wearable technology into workplace safety systems has emerged as a transformative solution for mitigating risks in hazardous environments. This study evaluates the effectiveness of IoT-enabled smart helmets equipped with real-time monitoring and early warning systems to enhance worker safety in industries such as mining, construction, and chemical processing. The smart helmet system integrates multiple sensors, including GPS modules for location tracking, gas detectors for environmental monitoring, temperature and humidity sensors for ambient condition assessment, and health monitoring sensors such as heart rate monitors and concussion detectors. Advanced edge AI algorithms are embedded to enable local data processing, ensuring low latency and rapid decision-making. The performance of the system was rigorously evaluated under controlled and simulated hazardous conditions, demonstrating high accuracy in location tracking (mean absolute error of 2.3 meters), gas detection (thresholds of 5 ppm for methane and 5,000 ppm for CO2), and health monitoring (97% accuracy for heart rate sensors). Battery efficiency was optimized through low-power hardware design and energy-saving strategies, achieving a continuous operational lifespan of up to 10 hours. Robust privacy and security measures, including AES-256 encryption and multi-factor authentication, ensured the protection of sensitive data. Despite these advancements, challenges such as scalability, adaptability to dynamic scenarios, and emerging cybersecurity threats remain areas for further exploration.